A review on teacher's perception towards the use of interactive whiteboard in classroom activities - Zulkifli Auni, Siti Hadijah; Md Khambari, Mas Nida; Ramli, Siti Nur Fadzlin; Lim, Shien Yee (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper aims to examine and review the existing literatures on teacher’s perception towards the use of interactive whiteboard in the classroom activities. The researchers had conducted the armchair analysis technique where previous studies related with the teacher’s perception on interactive whiteboard were collected and analyzed. The purpose of doing this is to facilitate the researchers to tract down the literatures and categorize them into belonging categories. The researchers had divided the content of this conceptual paper into three main sections. The first section explained about the introduction and study background of the interactive whiteboards. Second section talked about the integration of interactive whiteboards in education. In this section, the researchers had collected relevant articles to study about the interest topic which is on teacher’s perception towards the use of interactive whiteboard in classroom activities. There are no time boundary set since the researchers try to find the pattern of the study throughout the year. Next, the third section writes about the future of interactive whiteboard in an educational setting and how it can give impact in the teaching and learning process. Through all the literature reviews, the findings of this conceptual paper revealed that teachers perceive interactive whiteboard as an interactive learning tools that can be used to assist them in the instructional delivery. However, there are also negative perceptions highlighted especially in term of technical support and cost for maintaining the interactive whiteboard. From the research also, the researchers have recognized and categorized the most prominent themes that emerged from previous research conducted. As a whole, this paper summarizes the teacher’s perception on the integration of interactive whiteboard in the classroom activities by following the armchair analysis technique.